2017
DOI: 10.4049/jimmunol.1601736
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Density Dictates Immune Responsiveness following Red Blood Cell Transfusion

Abstract: Although RBC transfusion can result in the development of anti-RBC alloantibodies that increase the probability of life-threatening hemolytic transfusion reactions, not all patients generate anti-RBC alloantibodies. However, the factors that regulate immune responsiveness to RBC transfusion remain incompletely understood. One variable that may influence alloantibody formation is RBC alloantigen density. RBC alloantigens exist at different densities on the RBC surface and likewise exhibit distinct propensities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 70 publications
4
68
0
Order By: Relevance
“…[31][32][33] Further, we demonstrated that DHbA does directly impact CTT outcomes, as increased HbA clearance leads to lower pretransfusion Hb, higher HbS, and higher reticulocytes. Although the factors that dictate RBC alloimmunization continue to be an area of active investigation, [34][35][36][37][38][39] as patients with RBC antibodies have increased HbA clearance, it is possible that increased removal of transfused RBCs may reflect increased RBC uptake by immune cells that are uniquely poised to facilitate RBC alloimmunization. 40 Conversely, in a murine model of alloimmunization, donor RBCs that were subjected to pretransfusion oxidant stress to cause rapid posttransfusion clearance by the reticuloendothelial system were significantly more immunogenic than donor RBCs with longer posttransfusion survival, suggesting that clearance rate by the reticuloendothelial system influences alloimmunization respones.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Further, we demonstrated that DHbA does directly impact CTT outcomes, as increased HbA clearance leads to lower pretransfusion Hb, higher HbS, and higher reticulocytes. Although the factors that dictate RBC alloimmunization continue to be an area of active investigation, [34][35][36][37][38][39] as patients with RBC antibodies have increased HbA clearance, it is possible that increased removal of transfused RBCs may reflect increased RBC uptake by immune cells that are uniquely poised to facilitate RBC alloimmunization. 40 Conversely, in a murine model of alloimmunization, donor RBCs that were subjected to pretransfusion oxidant stress to cause rapid posttransfusion clearance by the reticuloendothelial system were significantly more immunogenic than donor RBCs with longer posttransfusion survival, suggesting that clearance rate by the reticuloendothelial system influences alloimmunization respones.…”
Section: Discussionmentioning
confidence: 99%
“…While proteolytic cleavage allowed HEL to be selectively removed in vitro , many proteins are sensitive to protease, which could impact RBC circulatory half‐life, interactions with immune cells or other RBC changes that may influence the overall immune response to HOD, precluding the use of this approach to examine the potential impact of HEL antigen levels on anti‐HOD formation. HOD founders that express different levels of HOD, as recently described for KEL, will ultimately be needed to begin defining potential antigen threshold requirements for a productive immune response against the HOD antigen.…”
Section: Discussionmentioning
confidence: 99%
“…For detection of Ter‐119, RBCs were stained with Ter‐119 (BD Biosciences), as done previously . To assess anti‐HOD immunoglobulin M (IgM) and IgG antibody development, sera were flow cross‐matched, as previously described . All antibodies were used at 1:100 in fluorescence activated cell sorting buffer (2% bovine serum albumin in phosphate‐buffered saline) unless otherwise noted, as done previously …”
Section: Methodsmentioning
confidence: 99%
“…A series of transgenic mice expressing variations of the human KEL glycoprotein have been generated over the past 5 years, with some expressing very low copy number (KEL lo ) and some expressing a more moderate copy number (KEL). Recipients transfused with KEL lo RBCs fail to mount a detectable humoral immune response , whereas those transfused with RBCs expressing a moderate copy number of KEL generate anti‐KEL alloantibodies after a single transfusion . Further, animals transfused with transgenic RBCs expressing very high copy numbers fail to mount a detectable response, unless treated with an adjuvant around the time of RBC exposure.…”
Section: Rbc Antigen Considerationsmentioning
confidence: 99%
“…However, these animals remain non‐alloimmunised upon subsequent exposure to hGPA RBCs in the presence of an adjuvant (which are otherwise immunogenic in naïve animals). This non‐responsiveness is antigen specific, with animals tolerised to hGPA or other RBCs capable of responding to RBCs expressing 3rd party antigens .…”
Section: Rbc Antigen Considerationsmentioning
confidence: 99%